Effect of Guided Inquiry Models and Open Inquiry of Wave and Sound Vibration Materials on Critical Thinking Ability in terms of Science Process Skills - Herdianna Indawati; Sarwanto Sarwanto; Sukarmin Sukarmin (Postgraduate, University of Mataram, 2023)
This type of research is Quasi-Experimental research used to determine the influence of guided inquiry learning and open inquiry of vibration, wave, and sturdy materials on critical thinking ability (CTA) in science process skills (SPS) of class VIII students. The study population was students of state junior high schools in Mojokerto City class VIII, and samples were used in two schools in each sub-district with four classes of 32 students each. The research technique used is random cluster sampling with CTA and SPS test instruments. The study found there is an influence of crithical thingking ability on guided and open inquiry learning models. The second result there is an influence of critical thinking ability on science process skills (SPS) high and low. The last result there is no interaction of the influence of critical thinking ability between inquiry learning models guided, open inquiry and SPS